Combined Infrared-Convective Drying of Murta (Ugni Molinae Turcz) Berries: Kinetic Modeling and Quality Assessment - Lemus-Mondaca, R (2013)
Murta (Ugni molinae Turcz) berries were dried under convective and combined convective-infrared conditions at 40, 50 and 60°C and 400-800 W in order to determine the drying characteristics and to compare the dried product s quality. To model the drying kinetics, seven mathematical equations were fitted to experimental data. According to statistical tests performed, the Midilli-Kuçuk model best fitted experimental data and was closely followed by the logarithmic model. Effective moisture diffusivity also showed dependency on drying conditions and varied between 7.59 × 10-10 to 44.18 × 10-10 m2/s and 11.34 × 10-10 to 85.41 × 10-10 m2/s for air-convective drying and combined infrared-convective drying. As to quality attributes of the berries, total surface color difference (?E) and total phenolic content (TPC) were determined. It was found that chromaticity coefficients a* and b* changed significantly, showing ?E to be dependent on the mode of heat supply. TPC under all drying conditions decreased and was significantly different from the initial value in fresh samples. However, at a constant drying temperature, an increase in infrared power enhanced retention of TPC in samples. In particular, working at 40°C/800 W resulted in dried samples with the highest TPC. © 2013 Copyright Taylor and Francis Group, LLC.